Cooperative Realistic Setting (RESIK) Assisted by Peer Tutors Have an Effect to Students’ Knowledge Competence in Mathematics - Ade Dian Valentina Kesuma Dewi; I Wayan Wiarta (Jurnal Ilmiah Sekolah Dasar, 2020)
The low competency of student mathematical knowledge was the main problem on this research. That was due to the lack of an effective learning models and the students in the class was still receivers it made the students become inactive. This study aimed to analyze the significant influence of the Cooperative Realistic Setting (RESIK) learning model assisted by peer tutors on the mathematics competence of the fifth grade of Elementary School. The type of research was quasi-experimental with a non-equivalent control group design. The population was 329 fifth grade students of Elementary School while the sample used was 70 students by using cluster random sampling technique. Data collection technique using multiple choice test instruments. The analysed data was normalized gain scores from the results of the pretest and posttest using the polled variance t-test. The result of tcount = 11.7563 and ttable = 1.9955 at α = 0.05 and dk = 68. Because tcount > ttable then H0 was rejected and Ha was accepted. It can be concluded that there was a significant influence of the Cooperative Realistic Setting (RESIK) learning model assisted by peer tutors on the mathematics competence of the fifth grade of elementary school. The results of this study can be used as reading material in further research designs.